Indirect doping of microstructures fabricated by two-photon polymerization with gold nanoparticles - Tribuzi, Vinicius; Corrêa, Daniel Souza; Avansi Junior, Waldir; Ribeiro, Caue; Longo, Elson [UNESP]; Mendonça, Cleber Renato (Optica Publishing Group, 2012)
Nanoplasmonics and metamaterials sciences are rapidly growing due to their contributions to photonic devices fabrication with applications ranging from biomedicine to photovoltaic cells. Noble metal nanoparticles incorporated into polymer matrix have great potential for such applications due to their distinctive optical properties. However, methods to indirectly incorporate metal nanoparticles into polymeric microstructures are still on demand. Here we report on the fabrication of two-photon polymerized microstructures doped with gold nanoparticles through an indirect doping process, so they do not interfere in the two-photon polymerization (2PP) process. Such microstructures present a strong emission, arising from gold nanoparticles fluorescence. The microstructures produced are potential candidates for nanoplasmonics and metamaterials devices applications and the nanoparticles production method can be applied in many samples, heated simultaneously, opening the possibility for large scale processes.